2011
DOI: 10.1021/jp201966d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static Magnetic Field on Electrolyte Solutions under Kinetic Condition

Abstract: Electrolyte solutions were exposed for different time to weak static magnetic field (MF) generated from a stack of magnets (B = 15 mT) at the flow rate of 1.4 mL/s. The conductivity was measured as a function of time following the application of MF. It was found that the changes in conductivity depend on the kind of electrolyte and the magnetic exposure time and are related to the thermodynamic function of hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Studies additionally have verified the efficiency of applying the CMF on the biological and enzymatic activity of microorganisms responsible for processes of wastewater treatment [3]. Aarthi et al demonstrated Flavobacterium species' pretreatment through sinusoidal MF seems to result in additional effective paper mill effluents degradation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies additionally have verified the efficiency of applying the CMF on the biological and enzymatic activity of microorganisms responsible for processes of wastewater treatment [3]. Aarthi et al demonstrated Flavobacterium species' pretreatment through sinusoidal MF seems to result in additional effective paper mill effluents degradation.…”
Section: Introductionmentioning
confidence: 98%
“…It has been established that exposure of aqueous salt solutions to the magnetic field (MF) causes crystallization of calcium forms into aragonite and vaterite. Aragonite and vaterite do not trigger scale deposition on walls of the fitting but in the complete volume of water, and the suspension existence formed is devoid of cementing properties [1][2][3].It appears, however, that procedures of magnetic treatment of fluids may be exploited in a profoundly broader scale, because with suitably selected parameters the method uses a progressive effect on various other properties of a fluid including anaerobic sludge's and wastewaters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the types and quantity of soluble substances within the liquid phase control the responsiveness of these solutions to an external MF . An external MF can induce a significant change in the microscopic properties of the exposed aqueous solutions . Otsuka and Ozeki have reported that strong MFs acting on pure distilled water under vacuum did not change its properties.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental result is in line with the findings of Hasaani, Hadi and Rasheed[51] who observed a similar reduction in electrical conductivity measurement in calcium-bicarbonate solution following exposure to a magnetic field. Furthermore, whilst evaluating the effect of magnetic field exposure on scale formation, Szczes, Chibowski, Hołysz and Rafalski[52], Holysz, Szczes and Chibowski[53] and Marcus[54] concluded that the hydration shell thickness of the bicarbonate and calcium ions are subject to manipulation by magnetic fields leading to changes in electrical conductivity measurement. Overall, the exposure of the ions to the magnetic field has increased the hydration shell thickness of the bicarbonate ions causing the reduced electrical conductivity measurements experienced within this test.…”
mentioning
confidence: 99%